Japan's Ancient Indic Heritage: A Review of "Hindu Deities Worshipped in Japan" by Benoy K. Behl: Text and photographs by Benoy K. Behl, with an essay on 'The Japanese Perspective' by Dr. Mihoko Hiraoka, co-researched by Sujata Chatterji, The Hindu Group Publishing Private Limited, 2019, ISBN 978-9387791312. (12th January 2022) - Kini-Singh, Amita
Benoy K Behl is an art historian, photographer and film-maker whose work aims at presenting a wider perspective in understanding the art of India and Asia. This book was published based on the research output of a photographic exhibition of the same name that the author produced for the Japan Foundation, New Delhi and on a film titled "Indian Deities Worshipped in Japan" also produced by the author for the External Publicity Division of The Ministry of External Affairs, Government of India.